2018
DOI: 10.1016/j.radcr.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent pigmented villonodular synovitis of the temporomandibular joint

Abstract: Pigmented villonodular synovitis is a benign but locally aggressive extra-articular tumor arising from the synovial membrane of tendons and bursae occurring near a joint space. Rarely, pigmented villonodular synovitis can involve the temporomandibular joint, which is emphasized in this paper. Diffuse and localized types have been described in the literature. The diffuse type involves the entire synovial membrane and infiltrates adjacent structures, which tend to be more aggressive and associated with a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…D-TGCT usually shows contrast enhancement after injection of gadolinium-based contrast agent; therefore, contrastenhanced MR imaging is useful for the diagnosis of D-GCT [7,[17][18][19]. In the present study, all five patients with nonhemophilic HS showed minimal to mild enhancement of the thickened synovium with superficial linear enhancement, whereas all four patients with D-TGCT showed moderate to severe enhancement.…”
Section: Discussionsupporting
confidence: 45%
“…D-TGCT usually shows contrast enhancement after injection of gadolinium-based contrast agent; therefore, contrastenhanced MR imaging is useful for the diagnosis of D-GCT [7,[17][18][19]. In the present study, all five patients with nonhemophilic HS showed minimal to mild enhancement of the thickened synovium with superficial linear enhancement, whereas all four patients with D-TGCT showed moderate to severe enhancement.…”
Section: Discussionsupporting
confidence: 45%